Generation of brilliant green fluorescent petunia plants by using a new and potent fluorescent protein transgene. Issue 1 (December 2018) - Chin, Dong; Shiratori, Ikuo; Shimizu, Akihisa; Kato, Ko; Mii, Masahiro; Waga, Iwao
Abstract The application of fluorescent proteins in ornamental plants has lagged behind despite the recent development of powerful genetic tools. Although we previously generated transgenic torenia plants expressing green fluorescent protein from marine plankton (CpYGFP), in which bright fluorescence was easily visible at the whole plant level, the maximum excitation of this protein within the visible light spectrum required the use of a coloured emission filter to eliminate exciting light. Here, to overcome this limitation, we generated transgenic petunia plants expressing eYGFPuv, a CpYGFP derivative exhibiting bright fluorescence under invisible ultraviolet (UV) light excitation, with a novel combination of transcriptional terminator plus translational enhancer. As expected, all transgenic plants exhibited brilliant green fluorescence easily visible to the naked eye without an emission filter. In addition, fluorescence expressed in transgenic petunia flowers was stable during long-term vegetative propagation. Finally, we visually and quantitatively confirmed that transgenic petunia flowers resist to long-term exposure of UV without any damages such as fluorescence decay and withering. Thus, our whole-plant fluorescence imaging tool, that does not require high sensitive imaging equipment or special imaging conditions for observation, might be useful not only for basic plant research but also for ornamental purposes as a novel flower property.